Intersex piglet with bilobed urinary bladder in Kumasi, Ghana: a case report (2017)
This paper reports a case of a true intersex in a pig in Kumasi, Ghana. The diagnosis was based on gross and histomorphological assessment of the genital organs which consist of a left ovary, two uterine horns and body of uterus, along with a right testis without an epididymis. Vagina and vulva were also absent. A perineal scrotal pouch and a tubular tract connection with an intra-abdominal urinary bladder conducting urine through a miniature paraphimotic sigmoid shaped penis were observed. A rectal prolapse was consequent to rectal compression by the inadequately voided urinary bladder. Gonadal hormonal profiles were analysed and compared in the true intersex and those of the males and female siblings using standard techniques. The embryologic, reproductive, and swine production cost implications of intersex were discussed